Does Sterilization Affect the Performance of Single-Step Resin Composite Polishers? - Christina Papadopoulou; Maria Anagnostou; Konstantinos Masouras; Vasileios Margaritis; Charikleia Paximada (MDPI AG, 2023)
(1) Background: Single-step polishers are used extensively for resin-composite polishing. The purpose of this study was to evaluate the effect of sterilization on their performance. (2) Methods: Optrapol Next Generation/Ivoclar-Vivadent, Jazz Supreme/SS White, Optishine Brush/Kerr and Jiffy Polishing Brush/Ultradent were used for polishing a nanohybrid resin composite (IPS Empress Direct/Ivoclar-Vivadent). Polishers (n = 40) were microscopically inspected before use. After polishing, surface roughness (Sa, Sz, Sdr, Sci) and gloss were determined. Polishers were subsequently sterilized and microscopically re-examined. The process was repeated four times on new samples (n = 200). Data were analyzed using the Friedman test and Wilcoxon post hoc test, at α = 0.05. (3) Results: Optrapol's performance improved after the first sterilization for Sa and gloss, whereas it declined after the fourth sterilization for Sa. Jazz's, improved after the second sterilization for Sa and gloss and after the third sterilization for Sdr. An improvement trend was observed for Optishine after the first sterilization, but not statistically significant. Sa, Sz, and gloss declined after the fourth sterilization. Jiffy's performance was inconsistent, with a trend of performance loss after the fourth sterilization. (4) Conclusions: Performance of all polishing systems improved after the initial sterilization, but deteriorated after the fourth sterilization cycle. However, their performance can be considered clinically acceptable for a longer period of use.